Кінетика та механізм інгібуючої дії фулерену C60 при окисненні гексаметилтриамідфосфату - Ковтун, Г.О.; Жила, Р.С.; Каменєва, Т.М. (Видавничий дім "Академперіодика" НАН України, 2008)
It has been shown that fullerene C60 terminates oxidation chains of hexamethylphosphoramide on the interaction with alkyl and peroxyl radicals. According to the kinetic researches, the rate constants k(ROO˙+ C60) = 9 · 10³l/(mol · s) and k(R˙+ C60) = 8.2 · 10^7 l/(mol · s) and the stoichiometric coefficient of termination of оxidation chains RH f = 5.4 ± 0.4 are estimated at 50 ºC, where R = (O)P[N(CH3)2]2N(CH3)CH2.